(untitled) (Bangladesh Journal of Genetics and Biotechnology, 2009)
Key words: Tobacco; potato; ADP-glucose pyrophosphorylase; TA29 and NTM19 promoter Bangladesh j. genet. biotechnol. 7(1&2): 43-48 2006 (June & December)